Memahami Transmisi Pendidikan Islam di Madrasah - Sumadi Sumadi (Journal of Education and Religious Studies, 2022)
Islamic education has been at the core of the intellectual development of Muslims for centuries. Madrasas, as traditional educational institutions in the Muslim world, play an important role in the transmission of Islamic scholarship from generation to generation. This abstract discusses the development of education in the transmission of Islamic scholarship in Madrasah by focusing on the changes and challenges faced by this education system. This study involves an analysis of the history of the development of Madrasah from early to modern times. The development of education in Madrasah includes the transformation of curriculum, teaching methods, and the integration of technology in the learning process. In addition, the role of teachers in transmitting authentic Islamic scientific knowledge is also a major concern in this study. In the context of globalization and advances in information technology, Madrasah is faced with various challenges, such as maintaining the relevance of traditional education in modern society and facing competition from the secular education system. Efforts to maintain the authenticity of Islamic values and integrate with contemporary educational approaches are one way to answer this challenge. The research also highlights the importance of Madrasah's role in fostering a deep understanding of Islam and increasing interfaith tolerance. Overall, the development of education in the transmission of Islamic scholarship in Madrassas presents an opportunity to explore the potential of Islamic education holistically and sustainably, and prepare future generations to become responsible global citizens with a strong Islamic scientific foundation.